Secondhand exposure to aerosol from electronic cigarettes: pilot study of assessment of tobacco-specific nitrosamine (NNAL) in urine - Jose M. Martínez-Sánchez; Montse Ballbè; Raúl Pérez-Ortuño; Marcela Fu; Xisca Sureda; José A. Pascual; Armando Peruga; Esteve Fernández (Elsevier, 2019)
Objective: To assess the levels of a tobacco-specific nitrosamine (NNAL) in non-smokers passively exposed to the second-hand aerosol (SHA) emitted from users of electronic cigarettes (e-cigarettes). Method: We conducted an observational study involving 55 non-smoking volunteers divided into three groups: 25 living at home with conventional smokers, 6 living with e-cigarette users, and 24 in control homes (smoke-free homes). We obtained urine samples from all volunteers to determine NNAL. Results: We detected NNAL in the urine of volunteers exposed to e-cigarettes (median:0.55 pg/mL; interquartile range: 0.26-2.94 pg/mL). The percentage of urine samples with quantifiable NNAL differed significantly among the three groups of homes: 29.2%, 66.7% and 76.0%, respectively (p = 0.004). Conclusions: We found NNAL nitrosamine in urine samples from people exposed to SHA from e-cigarettes. However, these results could be confirmed with more studies with larger sample sizes. Resumen: Objetivo: Evaluar los niveles de nitrosamina específica del tabaco (NNAL) en no fumadores expuestos pasivamente al aerosol emitido por usuarios de cigarrillo electrónico. Método: Estudio observacional de una muestra de 55 voluntarios no fumadores divididos en tres grupos: 25 que vivían en una casa con un fumador de tabaco convencional, 6 que vivían en una casa con un usuario de cigarrillo electrónico y 24 que vivían en casas controles (hogares libres de humo). Se obtuvo una muestra de orina de todos los voluntarios para determinar las concentraciones de NNAL. Resultados: Se detectaron valores de NNAL en los voluntarios expuestos al cigarrillo electrónico (mediana: 0,55 pg/ml; rango intercuartílico: 0,26-2,94 pg/ml). El porcentaje de voluntarios con concentraciones cuantificables de NNAL fue estadísticamente diferente entre los tres grupos de casas: 29,2%, 66,7% y 76%, respectivamente (p = 0,004). Conclusiones: Se encontraron valores de NNAL en los no fumadores expuestos pasivamente al aerosol del cigarrillo electrónico. Estos resultados tienen que confirmarse con muestras más grandes. Keywords: Biomarkers, Nitrosamines, Second-hand aerosol, Electronic cigarette, Palabras clave: Biomarcadores, Nitrosaminas, Aerosol de segunda mano, Cigarrillo electrónico